2007
DOI: 10.1016/j.brainres.2006.12.057
|View full text |Cite
|
Sign up to set email alerts
|

Selective impairments in implicit learning in Parkinson's disease

Abstract: The basal ganglia are thought to participate in implicit sequence learning. However, the exact nature of this role has been difficult to determine in light of the conflicting evidence on implicit learning in subjects with Parkinson's disease (PD). We examined the performance of PD subjects using a modified form of the serial reaction time task, which ensured that learning remained implicit. Subjects with predominantly right-sided symptoms were trained on a 12-element sequence using the right hand. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 32 publications
6
25
1
Order By: Relevance
“…Additionally, we used higher-order probabilistic sequences, which again, was to model the types of associations with which people come into contact frequently. Our findings are similar to other studies examining sequence learning in people with PD that have shown impaired learning compared to controls (Wilkinson et al, 2009; van Tilborg and Hulstijn, 2010; Schendan et al, 2013), but in previous work, sequences were often deterministic (Ferraro et al, 1993), or participants were tested off of medication (Seidler et al, 2007), so the present study adds to the literature by testing a different type of learning in medicated participants. Nonetheless, our decision to test PD participants while they were medicated limits our ability to determine whether our results are due to medication or the disease itself.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, we used higher-order probabilistic sequences, which again, was to model the types of associations with which people come into contact frequently. Our findings are similar to other studies examining sequence learning in people with PD that have shown impaired learning compared to controls (Wilkinson et al, 2009; van Tilborg and Hulstijn, 2010; Schendan et al, 2013), but in previous work, sequences were often deterministic (Ferraro et al, 1993), or participants were tested off of medication (Seidler et al, 2007), so the present study adds to the literature by testing a different type of learning in medicated participants. Nonetheless, our decision to test PD participants while they were medicated limits our ability to determine whether our results are due to medication or the disease itself.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with functions commonly attributed to the DLS/PP, studies of PD and learning have observed deficits and abnormalities in implicit and sequence learning (Carbon and Eidelberg, 2006; Jackson et al, 1995; Krebs et al, 2001; Siegert et al, 2006; Wilkinson and Jahanshahi, 2007; Wilkinson et al, 2009), automization (Ghilardi et al, 2009; Lehericy et al, 2005; Seidler et al, 2007; Wu and Hallett, 2005)-- particularly evident with increasing task difficulty or multi-tasking (Mentis et al, 2003a)-- and sensory-motor mapping (Helmich et al, 2010; Krebs et al, 2001; Marinelli et al, 2009; Smith and McDowall, 2006; Stefanova et al, 2000). Findings, however, are not uniform (Abbruzzese et al, 2009; Doyon, 2008; Nieuwboer et al, 2009; Siegert et al, 2006) with some studies reporting spared learning (eg., (Behrman et al, 2000; Cohen and Pourcher, 2007; Jordan and Sagar, 1994).…”
Section: Consensus and Controversy: Pinning Down Learning Deficitssupporting
confidence: 60%
“…Critically, this is experience- and learning- dependent. Associated with implicit, procedural learning (Barnes et al, 2005; Foerde et al, 2006; Jog et al, 1999; Packard and White, 1991; Packard and Knowlton, 2002; Poldrack et al, 2001; Willingham et al, 2002), the DLS/PP is widely believed to acquire stimulus-response (S-R) associations (Balleine et al, 2007; Balleine et al, 2009; Balleine and O’Doherty, 2010; Divac et al, 1967; Faure et al, 2005; Graybiel, 1998; Haruno and Kawato, 2006; Kimchi et al, 2009; Knowlton et al, 1996; Konorski, 1967; Mahon et al, 2004; Packard and Knowlton, 2002; Tang et al, 2007; Yin et al, 2004; Yin and Knowlton, 2006) that provide a substrate for skill learning (Benecke et al, 1987; Boyd et al, 2009; Graybiel, 1998; Hikosaka et al, 1999; Jog et al, 1999; Kermadi et al, 1993; Sakai et al, 2003; Seidler et al, 2007; Yin et al, 2009), especially automated and habitual responses (Balleine and O’Doherty, 2010; Costa, 2007; Doyon et al, 2009; Faure et al, 2005; Graybiel, 2008; Jog et al, 1999; Knowlton et al, 1996; Miyachi et al, 1997; Miyachi et al, 2002; Packard and Knowlton, 2002; Poldrack et al, 2005; Puttemans et al, 2005; Redgrave et al, 2010; Tang et al, 2007; Yin and Knowlton, 2006) that underlie rapid expression of behaviors under stimulus control to optimally match action selection and motor execution to on-going stimuli. As a putative substrate for action selection, the DLS/PP provides a mechanism for initiating, terminating and switching responses (Benecke et al, 1987; Cameron et al, 2009; Cools et al, 2004; Cools et al, 2006a; Cools et al, 2006b; Hikosaka and Isoda, 2010; Jin and Costa, 2010).…”
Section: Models Of the Basal Ganglia And The Pathophysiology Of Pdmentioning
confidence: 99%
“…Other SRT studies reported conflicting results. In fact, some showed impaired (Westwater et al 1998; Smith and McDowall 2004; Deroost et al 2006; Siegert et al 2006; Smith and McDowall 2006; Wilkinson and Jahanshahi 2007) and other preserved (Pascual-Leone et al 1993; Jackson et al 1995; Smith et al 2001; Kelly et al 2004; Seidler et al 2007) SRT learning in PD. The results of these studies are difficult to interpret.…”
Section: Pd and Sequence Learning With The Srt Taskmentioning
confidence: 98%
“…This is an important point in PD, as these patients heavily rely on external drives and cues and typically exhibit a decrement of self-drive, that can at least partially explain the non-significant difference between response times of SRT sequence and random blocks. Therefore, the “abnormal” lack of change in response time in SRT tasks could reflect a motor deficit (Westwater et al 1998; Deroost et al 2006; Seidler et al 2007) as well as a decreased self-drive and not an actual impairment in motor learning.…”
Section: Pd and Sequence Learning With The Srt Taskmentioning
confidence: 99%